FEATURES OF THE LEVEL OF MANIFESTATION OF GENETICALLY DETERMINED COMPONENTS OF SUCCESS OF QUALIFIED BASKETBALL PLAYERS (Physical Culture and Sport: Scientific Perspective, 2023)
In order to provide appropriate psychophysiological support for qualified basketball players, there is a need to develop informative criteria. After all, high indicators of the components of the psychophysiological state are correlated with the maximum mobilization of psychoemotional and functional reserves. The article presents the results of determining the characteristics of the level of manifestation of the genetically determined components of the success of qualified basketball players. The research was conducted using the "Multipsychometer-05" hardware and software computer complex. Tests were selected for a comprehensive study: a modified Stroop test was used to determine the dominance of the cerebral hemispheres, a modification of the questionnaire test by A. Mehrabian (1969), readapted by S. A. Shapkin to determine the level of motivation to achieve success in athletes, and a questionnaire for assessing hostility by A. Bass - A. Darkee adapted by L. Pochebut. Qualified basketball players aged 20-23 took part in the research. According to the results of scientific research on the characteristics of the level of expression of the activity-based genetically determined components of the success of qualified basketball players, it was found that according to the field independence values, all athletes in our sample show a slight shift towards the field dependence indicator, with an average level of manifestation of functional asymmetry and a qualitative indicator of the performance of the task; according to the level of motivation in the tested group, the level is higher than the average, and a tendency towards the predominance of the motivation to achieve success is noted; the analysis of indicators of various types of aggression proved that manifestations of verbal and physical aggression and auto-aggression are at an average level; instead, substantive and emotional aggression are at a low level. As for the integral indicator of aggressiveness of qualified basketball players, the average level of aggressiveness was also recorded.